Sweet Dezato Group / Muhd Hanif Abdul Ghani... [et al.] - Abdul Ghani, Muhd Hanif; Amir Hamzah, Anis Afeqah; Sallehuddin, Norsaleha; Sulaiman, Siti Maslinda (2012)
Our company, Sweet Dezato Groups is a company that concern about the demand and needs of Malaysians especially to those who are having busy lifestyle. Therefore, we provide an easier dessert for them to eat it everywhere they want. The customers just need to come to our shop and make their order. Thus, this kind of product can help satisfy the need of people. Besides that, we would make sure that the quality of the product will reach the expectation of the society with the good quality. Furthermore, we will make some upgrading in our product and others. We are not just looking for profits but we want to help people especially help our own country. With our product, we will provide the facility and also service to people. Our upgrade product will give better satisfaction to customers. It also can increase our country income by the tax that we pay and can also be an attractive to tourist with our service product. Moreover, we will create another job to citizen in Malaysia. We had decided to start our business at No. 13, Kompleks Komersial, Permatang Pauh, Lot 3823 Mukim Jalan Permatang Pauh 13500 Seberang Perai Tengah, Pulau Pinang. The reason why we choose these area because it located in town and also near to the office and have a lot people living there. So we think that this area are suitable for our dessert. Siti Maslinda bt Sulaiman has been appointed to be the General Manager. Administrative Manager is Muhammad Hanif b Abd Ghani as he is the best to hold this position. We also agreed to appoint Anis Afeqah bt Amir Hamzah to be the Marketing Manager due to her new ideas in promoting our business to the customers. Last but not least, Financial Manager is hold by Norsaleha bt Sallehuddin who is qualified for this position. For administrative plan, we try to manage the organization to meet the goals and objectives of the business. In the marketing plan, we will promote the business to the customers about our business and our company existence. Besides, the production of good products and maintaining the raw cost are under operation plan. In the financial, we will stabilize and maintain the company account. With the cooperation among us, we hope that our business will run efficiently and we can overcome all the challenges.